Pig behavior recognition and disease warning based on compressed sensing and long-short term memory network - Ren Wang; Mingdong Zhao (Journal of Applied Science and Engineering, 2025)
In order to solve the problems of low precision and poor stability in pig behavior recognition process due to the deficiency of environment and hardware conditions such as complex lighting conditions, close color of target and background, poor camera Angle and parameters, a compressed sensing recognition algorithm via long and short term memory network for optimized feature extraction is proposed in this paper. By means of ellipse fitting based on the minimum cost function and target tracking based on the shortest distance matching, we design four motion information detection algorithms including motion displacement, motion velocity, motion acceleration and motion angular velocity. The preliminary application of detecting daily active state, activity pattern and behavior recognition of pigs based on motion information is further explored. The improved k-means clustering algorithm is combined with convolutional neural network and long and short term memory network to provide early warning for pig diseases. The experimental results show that the detection error rate is lower than 10%, the proposed model has relatively higher recognition and prediction accuracy than other models.